A MULTICULTURE EDUCATION AND PERFORMANCE: A META ANALYSIS - Sari Budiarti (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2023)
This study aims to explore Multiculture Education and Performance through meta-analysis so that it can provide an alternative offer of better knowledge about Multiculture Education literature and performance in improving teacher performance which can support student success. The teacher is a facilitator for students to transfer knowledge in the classroom, moreover the existence of various cultures requires teachers to have high academic achievement, self-confidence, and self-motivation. This research was conducted to explore, examine and ensure the suitability of multicultural education and performance. This study uses a systematic review research method to investigate the concepts of multiculture education and performance in terms of definitions, antecedents, and outcomes. The literature search technique uses bibliometric techniques with the Vos Viewer application and sources search through the Scopus and Google Scholar databases with acquisitions from the 2017-2022 range, so the total articles searched for are 996 journals applied to Harzing's Publish or Perish edition 8.6.4198.8332 on the search date 08 November 2022. This literature review focuses on multiculture education to better understand the forms and features of such programs that contribute to teacher self-efficacy and success in working with culturally diverse students. Based on the explanation of the findings of the search for the articles above regarding the meta-analytic study between Multiculture and Performance, it can be concluded that several previous studies confirmed a positive relationship between Multiculture education and Performance, with the meta-analysis concluded that the average effect of multiculture education can increase performance by 0.24 or 24% which is included in the low category. While 76% is influenced by other variables